O muro dos outros e os outros do muro: alteridades e mundo árabe nas narrativas midiáticas - Paes, Ana Beatriz Pinto da Luz (2012)
Narratives are understood, in the common sense, as the practice of telling stories of the world or invented ones. Walls are canonical symbol of interdictions and limitations. Arabs and muslins are individuals traditionally linked to terrorism. In the present dissertation, we aim to show the narratives as world constructers, walls as potential relationship surfaces and the subject which concerns the arab world through a perspective that overcome the usual senses attributed to it. From the walls constructed by the Folha de São Paulo and Al Jazeera English, we reach to complexify the ways how the components of the arab world are walled in them, and through strategies as cultural translation and witnessing, notice the forms of constructing otherness and possible relationships. The proposal is to join the tridimensional trip, where we can experience the walls from above, below and beyond.